Isobaric Tags for Relative and Absolute Quantification-Based Proteomics Reveals Candidate Proteins of Fat Deposition in Chinese Indigenous Sheep With Morphologically Different Tails - Zhu, Caiye; Cheng, Heping; Li, Na; Liu, Tiaoguo; Ma, Youji (Frontiers in Genetics, 2021)
Background: Chinese indigenous sheep can be classified into three types based on tail morphology: fat-rumped and thin-tailed sheep, of which the typical breeds are Altay sheep and Tibetan sheep, respectively. Methods: To unravel the differential protein underlying the phenotypic differences among different type tails, we used iTRAQ combined with multi-dimensional liquid chromatography tandem mass spectrometry (LC-MS/MS) technology to detect candidate proteins, then combined with the database search, identified the differential protein; finally, the bioinformatics technology was used to perform GO analysis and KEGG partway analysis. Results: Of the total 3248 proteins were identified, among which 44 were up-regulated differentially expressed proteins and 40 were down-regulated differential proteins. After analysis of GO function and KEGG pathway, it is found that the functions of these differentially expressed proteins are mainly bingding, catalytic activity, structural molecule activity, molecular function regulator and transporter activity. Among these differentially expressed proteins, APOA2, GALK1, ADIPOQ and NDUFS4 are associated with fat formation and metabolism. Conclusions: APOA2, GALK1, ADIPOQ and NDUFS4 genes may be involved in the deposition of fat in the tail of sheep. This study provides a scientific basis for the breeding of thin-tailed sheep.